2000
DOI: 10.1002/1097-0177(200007)218:3<480::aid-dvdy1011>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the odontoblast differentiation process in vitro by a combination of FGF1, FGF2, and TGF?1

Abstract: Isomere Fullerentrimere wurden mechanochemisch hergestellt und Langmuir‐Filme von ihnen auf Au(111)‐Oberflächen durch Rastertunnelmikroskopie (RTM) untersucht. Jedes der Isomere zeichnet sich durch eine andere Oberflächenmorphologie aus. Die beobachtete Verteilung der Isomere ist im Einklang mit MO‐Rechnungen zu ihrer Stabilität. Durch RTM können die einzelnen Isomere unterschieden werden (Beispiel siehe Bild), was mit spektroskopischen Methoden schwierig ist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 30 publications
0
40
0
1
Order By: Relevance
“…Treatment with TGF-β1 and fibroblast growth factor-1 (FGF-1) or BMP-2 induces the differentiation of odontoblasts from dental papilla cells as well as synthesis of the dentin matrix (29,27). The mRNA expression of TGF-β1 and noncollagenous proteins such as ON and BSP is increased in secretory odontoblasts in the advanced bell stage during mouse tooth development (26).…”
Section: A B Cmentioning
confidence: 99%
“…Treatment with TGF-β1 and fibroblast growth factor-1 (FGF-1) or BMP-2 induces the differentiation of odontoblasts from dental papilla cells as well as synthesis of the dentin matrix (29,27). The mRNA expression of TGF-β1 and noncollagenous proteins such as ON and BSP is increased in secretory odontoblasts in the advanced bell stage during mouse tooth development (26).…”
Section: A B Cmentioning
confidence: 99%
“…The beads were implanted into the mesoderm of chick wing buds in ovo or mouse forelimbs in vitro, in the position, and for the time, desired. Mouse embryo trunk fragments with forelimbs were cultured either in a medium-air interface system (Zuniga et al, 1999) or ventral side down on semisolid medium (Unda et al, 2000). For all experiments, beads soaked in the corresponding vehicle were used as control; their application never resulted in modification of gene expression.…”
Section: Application Of Proteins Using Beads As Carriersmentioning
confidence: 99%
“…Similarly, Bmp-4 is expressed by odontoblasts (Bègue-Kirn et al 1994) and in the IDE, where it appears to persist longer than Bmp-2 (Aberg et al 1997). Using in vitro functional approaches, it has been shown that TGF ␤ 1 and -3, BMP-2, and BMP-4 can induce odontoblast differentiation (Bègue-Kirn et al 1992;Ruch 1998;Unda et al 2000). The relative amount of BMP-2 and, to a lesser extent, BMP-4 increased from E17 to E19.…”
Section: Late Bell Stage and Cytodifferentiationmentioning
confidence: 99%